2011
DOI: 10.1038/srep00206
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular complexity determines the number of olfactory notes and the pleasantness of smells

Abstract: One major unresolved problem in olfaction research is to relate the percept to the molecular structure of stimuli. The present study examined this issue and showed for the first time a quantitative structure-odor relationship in which the more structurally complex a monomolecular odorant, the more numerous the olfactory notes it evokes. Low-complexity odorants were also rated as more aversive, reflecting the fact that low molecular complexity may serve as a warning cue for the olfactory system. Taken together,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…When human smells an odorant, olfactory neurons (as receptor cells) detect odor molecules and transmit information about the odor to the brain in a process called sensory transduction which yields to perception46. Based on the research done by Kermen et al 47,. high complexity odorants activate more types of olfactory receptor than low complexity odorants.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…When human smells an odorant, olfactory neurons (as receptor cells) detect odor molecules and transmit information about the odor to the brain in a process called sensory transduction which yields to perception46. Based on the research done by Kermen et al 47,. high complexity odorants activate more types of olfactory receptor than low complexity odorants.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The dotted line represents the p < 0.05 significance threshold with respect to random predictions. The performance of four equations for pleasantness prediction suggested by Zarzo (10) [from top to bottom: equations (10, 9, 11, 7, 12)] and of a linear model based on the first seven principal components inspired by Khan et al (8) are shown.…”
Section: Figmentioning
confidence: 99%
“…Pleasantness was predicted most accurately using a mix of both Dragon and Morgan/NSPDK features. For example, pleasantness correlated with both molecular size (r = .160 p < 10 −3 ) (9), and similarity to paclitaxel (r = 0.184 p < 10 −4 ) and citronellyl phenylacetate (r = 0.178 p < 10 −4 )(Fig. S6b).…”
mentioning
confidence: 99%
“…Whereas psychophysical investigations have shown that such hedonic processing of smells is influenced by physicochemical properties (Khan et al, 2007; Mandairon et al, 2009; Poncelet et al, 2010; Joussain et al, 2011; Kermen et al, 2011; Zarzo, 2011), many other experiments, however, showed that odor pleasantness can be modulated by physiological (Fernandez et al, 2013; Joussain et al, 2013a,b) or cognitive factors (Herz, 2003; Rolls, 2004; de Araujo et al, 2005; Barkat et al, 2008; Rinck et al, 2011). For example, it has been shown that pleasantness judgments are enhanced when subjects are able to identify the odorant source (Ayabe-Kanamura et al, 1998).…”
Section: Introductionmentioning
confidence: 99%